REINTERPRETASI PERKAWINAN USIA ANAK-ANAK: Menafsir Ulang Teks-Teks Keagamaan Tentang Perkawinan Anak - Abdul Aziz (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2019)
This article is intended to explain the answers about the negative and positive sides of child marriage which are sourced from religious texts. Some Muslim communities consider that marriages at the age of children can cause problems that can ease the economic burden of parents as well as to immediately obtain offspring and stay away from free sex. Others consider that child marriages will cause harm, both physical-biological, psychological, economic, and other impacts. Physically, biologically, the tools of reproduction of minors are still in the process of maturing, so they are not ready to have sexual relations, especially if they are pregnant and giving birth. It should be that religious texts and science go hand in hand without contradicting one another. This article also explains the role of education as a solution in solving community problems related to child marriage.